A novel liposomal formulation of FTY720 (Fingolimod) for promising enhanced targeted delivery - Mao, Yicheng (2013)
We describe here the development and characterization of the physicochemical and pharmacokinetic properties of a novel liposomal formulation for FTY720 delivery, LP-FTY720. The mean diameter of LP-FTY720 was ~157 nm, and the FTY720 entrapment efficiency was ~85%. The liposomal formulation protected FTY720 from degradation in aqueous buffer and showed toxicity in CLL patient B cells comparable to that of free FTY720. Following intravenous injection in ICR mice, LP-FTY720 had an increased elimination phase half-life (~28 vs. ~19 hr) and decreased clearance (235 vs. 778 mL/h/kg) compared to the free drug. Antibodies against CD19, CD20 and CD37 were incorporated into LP-FTY720, which provided targeted delivery to CLL patient B cells and thus achieved higher killing efficacy. The novel liposomal carrier of FTY720 demonstrated improved pharmacokinetic properties, comparable activity, and a potential platform for targeted delivery to CLL by overcoming the limited application of free FTY720 to B malignancy treatment.